Semantic and pragmatic precision in conversational AI systems - Bunt, Harry; Petukhova, Volha (Frontiers in Artificial Intelligence, 2023)
For a conversational agent, to display intelligent interactive behaviour implies the ability to respond to the user's intentions and expectations with correct, consistent and relevant actions of appropriate form and content in a timely fashion. In this paper, we present a data-driven analytical approach to embed intelligence into a conversational AI agent. The method requires a certain amount of (ideally) authentic conversational data, which is transformed in a meaningful way to support intelligent dialogue modelling and the design of intelligent conversational agents. These transformations rely on the ISO 24617-2 dialogue act annotation standard, and are specified in the Dialogue Act Markup Language (DiAML), defined as part of the standard and extended with plug-ins for articulate representations of domain-specific semantic content and customised communicative functionality. ISO 24617-2 is shown to enable systematic in-depth interaction analysis and to facilitate the collection of conversational data of sufficient quality and quantity of instances of interaction phenomena. The paper provides the theoretical and methodological background of extending the ISO standard and DiAML specifications for use in interaction analysis and conversational AI agent design. The {\em expert-assisted} design methodology is introduced, with example applications in the healthcare domain, and is validated in human-agent conversational data collection experiments.